The Forty Rules of Love: a Mystical Eliadean Perspective - Elham Mohammadi Achachelooei (مطالعات بین‌رشته‌ای ادبیات، هنر و علوم انسانی)
This interdisciplinary study is a mystical reconsideration of Elif Shafak’s The Forty Rules of Love (2011), FRL hereafter, based on the theologian Mircea Eliade’s perspective on the notion of sacred life as hierophany. Considering the huge bulk of reviews analyzing the Eastern Sufi aspect of the novel as a mystical stand, this investigation probes the compatibility of Eliade’s Universalist spiritual stand with the Sufi perspective reflected in the novel, considering the Islamic tradition through focusing on Maulana’s mystical transformation via Shams of Tabriz. It also pays attention to the Western cultural manifestations absent in most of the reviews and considers the Orientalist features attributed to the novel by some critics. The investigation concludes that the form of Sufism represented in the novel is close to Maulana’s original perspective, and there is a spiritual congruity between Maulana’s Islamic stand, being affected by Ibn Arabi, and Eliade’s Western Christian one. This justifies the depiction of the characters’ mystical transformation within FRL as being touched by Islamic principles and not totally submissive before the Orientalist discourse.